2021
DOI: 10.1126/sciadv.abe9924
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective and high-performance osmotic power generators in subnanochannel membranes enabled by metal-organic frameworks

Abstract: The electric organs of electric eels are able to convert ionic gradients into high-efficiency electricity because their electrocytes contain numerous “subnanoscale” protein ion channels that can achieve highly selective and ultrafast ion transport. Despite increasing awareness of blue energy production through nanochannel membranes, achieving high-performance energy output remains considerably unexplored. Here, we report on a heterogeneous subnanochannel membrane, consisting of a continuous UiO-66-NH2 metal-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(97 citation statements)
references
References 46 publications
2
89
0
1
Order By: Relevance
“… 221–223 For example, for nanoporous membranes based on metal–organic frameworks (MOF) with pore sizes around 6–7 Å it was shown that counter-ions with a size lower than the pore size of the MOF are able to pass through the MOF porosity yielding higher ion fluxes and selectivity. 224 Consistently, the transport across the porous MOF in the case of counter-ions with larger hydrated sizes is more restricted which leads to a detriment in the power capabilities. Quantitative results of different upscaled MOF-based membranes will be addressed in more detail in Section 7.2.…”
Section: Enhanced Nanofluidic Osmotic Energy – the Impact Of Structural And Experimental Variables On Sge Performancementioning
confidence: 99%
See 2 more Smart Citations
“… 221–223 For example, for nanoporous membranes based on metal–organic frameworks (MOF) with pore sizes around 6–7 Å it was shown that counter-ions with a size lower than the pore size of the MOF are able to pass through the MOF porosity yielding higher ion fluxes and selectivity. 224 Consistently, the transport across the porous MOF in the case of counter-ions with larger hydrated sizes is more restricted which leads to a detriment in the power capabilities. Quantitative results of different upscaled MOF-based membranes will be addressed in more detail in Section 7.2.…”
Section: Enhanced Nanofluidic Osmotic Energy – the Impact Of Structural And Experimental Variables On Sge Performancementioning
confidence: 99%
“… 169,218,219,250–255 Liu et al developed a highly selective nanoporous membrane based on the integration of the MOF UiO-66-NH 2 onto the surface of a highly ordered AAO membrane (UiO-66-NH 2 –AAO). 224 The composite membrane was created by in situ growth of the MOF UiO-66-NH 2 onto a pre-synthesized AAO membrane modified with 3-triethoxysilylpropylamine (APTES). The previous modification of the AAO membrane with the APTES is a crucial step since it acts as a crosslinker enabling the successful integration of the MOF.…”
Section: Towards the Construction Of Nred Platforms With Technological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies provide information on the synthesis and properties of MOFs. [4][5][6][7][8][9][10][11][12] Chueh et al [13] investigated the application prospect of MOFs in solar cells. Konnerth et al [14] reviewed the application of MOFs derived catalysts; MOFs have great application prospects in different fields because of their unique structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Through synthesis or design by simulation (Konnerth et al, 2020), the joints (including transition metals, post-transition metals and lanthanides) and linkers (such as Bi, tricarboxylate contained benzene ring, and N-contained cycloalkane composites) have different combinations, resulting in different texture properties and morphologies of MOFs (Tranchemontagne, Mendoza-Cortes, O'Keeffe, & Yaghi, 2009). At present, MOFs are widely used in catalysis (Liao et al, 2020), sensors (Chueh et al, 2019), osmotic power generator (Liu, Yeh, Zheng, & Wu, 2021), gas separation and purification (Lai et al, 2019), and gas storage (Alezi et al, 2015). Compared with traditional inorganic porous materials, MOFs have higher porosity, specific surface area, and more abundant functional sites (Banerjee, 2012;Xue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%